A switchable system between magnetic and natural circularly polarised luminescence via J-aggregation using photosynthetic antenna model compounds. Issue 8 (25th January 2023) - Tomikawa, Toranosuke; Kitagawa, Yuichi; Yoshioka, Koki; Murata, Kei; Miyatake, Tomohiro; Hasegawa, Yasuchika; Ishii, Kazuyuki
Abstract : Using zinc-chlorin, the switching of MCPL/CPL via J-aggregation has been clearly demonstrated for the first time. Abstract : A switchable system between magnetic and natural circularly polarized luminescence via J-aggregation using photosynthetic antenna model compounds is demonstrated for the first time. The J-aggregation provides characteristic dispersion-type circularly polarised luminescence signals based on the degenerate J-band ( g CPL = 0.03).